A Calmodulin-Like Gene (GbCML7) for Fiber Strength and Yield Improvement Identified by Resequencing Core Accessions of a Pedigree in Gossypium barbadense - Zhao, Nan; Wang, Weiran; Jiang, Kaiyun; Grover, Corrinne E.; Cheng, Cheng; Pan, Zhuanxia; Zhao, Cunpeng; Zhu, Jiahui; Li, Dan; Wang, Meng; Xiao, Li; Yang, Jing; et al. (Frontiers in Plant Science, 2022)
As a primary goal, Sea Island cotton (Gossypium barbadense) is world-renowned for its superior natural fiber. Although fiber strength is one of the most important fiber quality traits, genes contributing to fiber strength are poorly understood. Production of sea island cotton also is inextricably linked to improving its relatively low yield, thus enhancing the importance of joint improvement of both fiber quality and yield. We used genomic variation to uncover the genetic evidence of trait improvement resulting from pedigree breeding of Sea Island cotton. This pedigree was aimed at improving fiber strength and yielded an elite cultivar, XH35. Using a combination of GWAS and selection screens, we detected 82 putative fiber-strength-related genes. Expression analysis confirmed a calmodulin-like gene, GbCML7, which enhanced fiber strength in a specific haplotype. This gene is a major-effect gene, which interacts with a minor-effect gene, GbTUA3, facilitating the enhancement of fiber strength in a synergistic fashion. Moreover, GbCML7 participates in the cooperative improvement of fiber strength, fiber length, and fiber uniformity, though a slight compromise exists between the first two of these traits and the latter. Importantly, GbCML7 is shown to boost yield in some backgrounds by increasing multiple yield components to varying degrees, especially boll number. Our work provides valuable genomic evidence and a key genetic factor for the joint improvement of fiber quality and yield in Sea Island cotton.